Digital literacy and community empowerment in rural areas: A participatory action research in bringin village, Indonesia - Novianto Puji Raharjo; Mohammad Rofiuddin (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
Rural communities in many developing countries face persistent economic vulnerability due to limited access to technology, information, and market networks. This study aims to examine how the integration of digital media literacy and participatory education can contribute to rural economic empowerment. The research employs a qualitative approach using Participatory Action Research (PAR) conducted in Bringin Village, Tuban Regency, Indonesia. Community members, including youth groups, housewives, village officials, and BUMDes managers, were actively involved in the research process through participatory observation, focus group discussions, and semi-structured interviews. The intervention included digital marketing training, local product processing, and mentoring in social media-based entrepreneurship using soursop as a local resource. The findings indicate that digital literacy training significantly improved community capacity to market products independently, expand market reach, and increase the added value of local commodities. The emergence of the “Sirsak Toyyib” initiative illustrates how digital platforms can transform traditional agricultural products into marketable micro-enterprises. This study contributes to the development of a community empowerment model that integrates participatory education, local cultural values, and digital technology. The findings suggest that combining participatory approaches with digital literacy initiatives can foster sustainable economic transformation in marginalized rural communities.